When Justice Fails: Class Struggle and Violence in Kendrick Lamar’s XXX. through a Marxist Lens - Joice Anita Siburian; T. Thyrhaya Zein; Yulia Rahma Silalahi; Priskila Anggi Marpaung; Rolan Siallagan; Yosia Situmorang (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This study examines Kendrick Lamar’s song XXX. from the album DAMN. (2017) through a Marxistliterary perspective to explore the representation of class struggle, violence, and social inequality incontemporary hip-hop music. While previous studies have primarily focused on race and identity inhip-hop, limited attention has been given to the intersection of social class and violence withinspecific musical texts. Using a qualitative research design, the study analyzes selected lyrics ascultural texts that reflect power relations, ideology, and institutional failure. The findings reveal thatviolence in XXX. is portrayed not merely as an individual reaction but as a consequence of structuralinequality, limited access to justice, and class oppression. Furthermore, the song exposes ideologicalcontradictions within capitalist society and critiques the failure of institutions to protect marginalizedcommunities. The study concludes that hip-hop functions as an influential medium of social criticism,highlighting systemic injustice and the need for greater social equity and institutional accountability.Keywords: Marxism, class struggle, social inequality, violence, ideology, hip-hop, Kendrick Lamar,XXX., systemic injustice.